(untitled) (Revista Brasileira Multidisciplinar, 2025)
The current urban expansion and the continuous increase in vehicles on the road system make traffic engineering crucial in modeling sustainable solutions for urban mobility. However, this field of knowledge dedicated to the study and management of vehicular flow faces increasing challenges arising from the complexity of road traffic. Traffic microsimulation, an advanced computational tool, offers the opportunity to evaluate traffic behavior in detail and the effectiveness of infrastructure projects and mobility policies. In this context, the objective of this paper is to assess the road capacity and the Level of Service (LOS) of the “S Curve” Viaduct (Praia Grande-SP, Brazil) and its surroundings, considering operational changes related to road characteristics and the vehicle flow in different periods of analysis. Traffic microsimulations were carried out using the VISSIM software, in which four models were applied for two distinct periods, the current one (2023) and the end of a 20-year time horizon (2043). In the first model, the previous operation of the viaduct was evaluated; the second and third models addressed the current operation, differing only in the access priority to the SP-055 Highway; and in the fourth model, the duplication already planned for the viaduct was considered. The results indicate that only the fourth model would result in satisfactory operational conditions for current traffic (2023). As for predicted traffic (2043), all models suggest some level of congestion, although these less satisfactory results may be associated with system overload in information processing. Future work is encouraged to calibrate the software parameters, and further investigate trends in the region.